1984
DOI: 10.1080/0361697840080116
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Collective Bargaining on Faculty Compensation in Community Colleges

Abstract: This study examines the impact of collective bargaining on faculty compensation at two-year colleges over the period 1970-81. The results show that faculty at unionized community colleges have not experienced significantly greater increases in compensation than their nonunionized brethren. In fact, the nonunion institutions actually experienced higher relative gains in compensation for the first three years after the unionized colleges first engaged in collective bargaining.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1991
1991
1993
1993

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 5 publications
(10 reference statements)
0
2
0
Order By: Relevance
“…1 after unionization and during the first few years of unionization dwindled significantly over time (Birnbaum, 1976;Morgan & Kearney, 1977;Leslie & Hu, 1977;Wiley, 1993). Specifically, two of the studies clearly reported that unionism had a favorable impact during the first five years of collective bargaining (Marshall, 1979;Baker, 1984). Afterwards, the trend was reversed in favor of nonunion colleges (Marshall, 1979).…”
Section: ~Shesmentioning
confidence: 89%
See 1 more Smart Citation
“…1 after unionization and during the first few years of unionization dwindled significantly over time (Birnbaum, 1976;Morgan & Kearney, 1977;Leslie & Hu, 1977;Wiley, 1993). Specifically, two of the studies clearly reported that unionism had a favorable impact during the first five years of collective bargaining (Marshall, 1979;Baker, 1984). Afterwards, the trend was reversed in favor of nonunion colleges (Marshall, 1979).…”
Section: ~Shesmentioning
confidence: 89%
“…In another study, Baker (1984) developed 31 matched pairs of union and nonunion community colleges based on four criteria: AAUP category, compensation level, size (number of full-time faculty), and geographic location. Compensation changes were compared over a five-year period relative to a base year .…”
Section: ~Shesmentioning
confidence: 99%